'Someone should oversee it': patient perspectives on the ethical issues arising with the regulation of probiotics. (28th December 2012) - Harrison, Krista L.; Farrell, Ruth M.; Brinich, Margaret A.; Highland, Janelle; Mercer, MaryBeth; McCormick, Jennifer B.; Tilburt, Jon; Geller, Gail; Marshall, Patricia; Sharp, Richard R.
Abstract: Background: Although many probiotic products are currently available in yogurt or pill form in the United States (US), there is uncertainty surrounding the structure of regulation of these products. As more therapeutic probiotics are developed, changes to existing regulatory process in the United States may be required to meet the needs of patients and users in the population. Objective: This study examined how patients with chronic gastrointestinal (GI) diseases view the regulation of probiotics. Design: We conducted a multi‐site qualitative study consisting of focus groups of patients with chronic gastrointestinal diseases at three tertiary hospitals: at [institutions removed for blinded review]. Results: We conducted 22 focus groups with 136 patients with major gastrointestinal (GI) diseases between March and August 2009. Participants were not familiar with the existing regulation of probiotic products but wanted assurances of accurate labelling of strain as well as safety. Participants raised concerns that regulation of probiotics might be accompanied by greater costs, reduced access and increased involvement of pharmaceutical companies. Although participants voiced significant doubt of government regulators, they felt that products containing genetically modified probiotic strains should have oversight comparable to that of pharmaceutical drugs. Discussion and conclusion: If GI patient perspectives are indicative of public perceptions of therapeutic probiotics in the United States, consumers may expect more rigorous regulation in the future while simultaneously wanting low costs, easy access and low involvement of pharmaceutical companies. Manufacturers, translational scientists, clinicians and regulators should be sensitive to consumer attitudes when designing, testing and regulating new therapeutic probiotics.